A critical role for cystathionine-β-synthase in hydrogen sulfide-mediated hypoxic relaxation of the coronary artery - Donovan, J.; Wong, P.S.; Roberts, Richard E.; Garle, M.J.; Alexander, Stephen P.H.; Dunn, William R.; Ralevic, Vera (Elsevier, 2017)
Hypoxia-induced coronary artery vasodilatation protects the heart by increasing blood flow under ischemic conditions, however its mechanism is not fully elucidated. Hydrogen sulfide (H2S) is reported to be an oxygen sensor/transducer in the vasculature. The present study aimed to identify and characterise the role of H2S in the hypoxic response of the coronary artery, and to define the H2S synthetic enzymes involved. Immunoblotting and immunohistochemistry showed expression of all three H2S-producing enzymes, cystathionine-β-synthase (CBS), cystathionine-γ-lyase (CSE) and 3-mercaptopyruvate sulfurtransferase (MPST), in porcine coronary artery. Artery segments were mounted for isometric tension recording; hypoxia caused a transient endothelium-dependent contraction followed by prolonged endothelium-independent relaxation. The CBS inhibitor amino-oxyacetate (AOAA) reduced both phases of the hypoxic response. The CSE inhibitor dl-propargylglycine (PPG) and aspartate (limits MPST) had no effect alone, but when applied together with AOAA the hypoxic relaxation response was further reduced. Exogenous H2S (Na2S and NaHS) produced concentration-dependent contraction followed by prolonged relaxation. Responses to both hypoxia and exogenous H2S were dependent on the endothelium, NO, cGMP, K+ channels and Cl−/HCO3 − exchange. H2S production in coronary arteries was blocked by CBS inhibition (AOAA), but not by CSE inhibition (PPG). These data show that H2S is an endogenous mediator of the hypoxic response in coronary arteries. Of the three H2S-producing enzymes, CBS, expressed in the vascular smooth muscle, appears to be the most important for H2S generated during hypoxic relaxation of the coronary artery. A contribution from other H2S-producing enzymes only becomes apparent when CBS activity is inhibited.